Studi Hukum Pidana dalam Kaitannya dengan Penambang Pasir Laut Ditinjau dari Undang-Undang Nomor 1 Tahun 2014 tentang Perubahan Atas Undang-Undang Nomor 27 Tahun 2007 tentang Pengelolaan Wilayah Pesisir dan Pulau-Pulau Kecil : Studi Kasus Kabupaten Alor - Rominaldo Lezhera Letfa; Jimmy Pello; Darius A. Kian (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
East Nusa Tenggara Province in managing the Coastal area in East Nusa Tenggara in Community participation in environmental protection and management efforts in East Lembur Village, Lembur District is still relatively low because not all communities play a role in the planning, implementation, utilization and evaluation stages in the context of environmental protection and management efforts. that the management of coastal areas must have permission from the local government and if carried out illegally, it can be subject to strict sanctions. The research method used in this study is empirical juridic research. Empirical legal research that focuses on behaviors that are embraced or developed in society. This behavior is accepted and appreciated by the community because it is not prohibited by statute law, does not contradict the morals of the community (social ethics). The results of this study show that the Criminal Law Regulation Related to Sea Sand Mining Based on Law No. 32 of 2024 Jo. Law No. 5 of 1990 Law Number 32 of 2024 concerning Amendments to Law Number 5 of 1990 provides a stronger legal framework for the management and protection of natural resources, including sea sand mining. The Coastal Rights Law refers to regulations and policies that regulate the utilization, management, and protection of coastal areas and the rights of the people living around them. that the people in East Lembur Village have several factors that cause why they are still doing illegal sand mining. One of the negative aspects is the implementation of mining activities that are not in accordance with existing regulations, such as illegal or unlicensed mining. Both on a large and small scale, mining activities require official permits, because their implementation without a permit can result in legal consequences that need to be accounted for.